A truncated palytoxin analogue, palytoxin carboxylic acid, isolated as an insecticidal compound from the red alga, Chondria armata. Issue 50 (12th December 2018) - Mori, Shoko; Sugahara, Kohtaro; Maeda, Mitsuru; Shimamoto, Keiko; Iwashita, Takashi; Yamagaki, Tohru
Graphical abstract: Highlights: A truncated palytoxin analogue was isolated from a red alga, Chondria armata . This compound showed half of lethal activity of palytoxin against cockroaches. The physicochemical properties of this compound were characterized. Abstract: Palytoxin (PTX) has been widely studied owing to its outstanding toxic properties and complex structural features. It is a great challenge to identify and isolate analogues of PTX from various organisms and reveal their physiological activities. We previously reported the isolation of PTX as an insecticidal compound from the red alga, Chondria armata . In this study, we investigate another active compound from C. armata, which has similar toxicity and chromatographic behavior as PTX. Our detailed structural analysis reveals that this compound is palytoxin carboxylic acid. We characterized its physicochemical properties and conducted extensive NMR studies. This analogue has a structure devoid of the terminus of PTX, such that its presence in the alga implies the role of symbiotic microorganisms in marine ecosystems.